Review of the trends, evolution, and future research directions of green hydrogen production from wastewaters – Systematic and bibliometric approach - Flavio Odoi-Yorke; Ephraim Bonah Agyekum; Mustafa Tahir; Agnes Abeley Abbey; Pradeep Jangir; Farhan Lafta Rashid; Hussein Togun; Wulfran Fendzi Mbasso (Energy Conversion and Management: X)
For today’s society, recognizing and identifying a sustainable energy source is crucial. The public, government, and business community have all expressed strong support for hydrogen energy, establishing it as a key fuel source for the future. This paper analyzes the state of wastewater for green hydrogen production research, focusing on global trends, evolution, potential hotspots, and future directions, using a systematic, bibliometric, and organized review of research publications from 2013 to 2023 in the Scopus database. The visualization and quantitative evaluation of the data was conducted using the VOSviewer software, and the Biblioshiny package in the R-software. The study also compared the various techniques that are used for the production of hydrogen using wastewaters. The research field experienced a 32.88 % annual growth, with 1,883 authors and 27.95 % international collaborations. Microbial photoelectrochemical cell, a recent energy generation technology, has gained interest due to its ability to treat various pollutants. This surge is attributable to technological advancements in wastewater hydrogen production, as part of global efforts to tackle environmental issues. This study advances knowledge and practices in the field of green hydrogen production using wastewater by illuminating new trends and intersecting themes. Potential future research directions on the topic were identified and proposed in this study.